Pembelajaran Berkarakter Berdasarkan Kurikulum Berbasis Kompetensi - Supriyono, (Pendidikan Sekolah Dasar, 2010)
Until recently, the condition of the learning system in our country, still colored by the approach which focuses on conventional learning models such as lectures, question and answer, and giving tasks, making it less able to stimulate students to engage actively in the learning process. In elementary school, education shows more and more indications that the pattern of learning teacher centered. Thus the tendency of learning, resulting in poor self-development potential in learning that students achieved learning achievement is not optimal. Impression of the prominence of verbal in the implementation of classroom teaching and learning activities are still too strong. To solve the above problems and to achieve maximum educational goals, the role is very important teachers and teachers are expected to have a way / model of good teaching and learning model capable selecting appropriate and in accordance with the concepts of the subjects that will be delivered. Education should learn to fruition in the form of changes in knowledge, and skills that are in line with institutional goals. As described in the Curriculum 1994, that the education in primary schools aims: (1) educate students to become fully human Indonesia based on Pancasila is able to build himself and take responsibility for the nation-building, (2) provide the capacity needed students to continuing higher education level, and (3) provide basic skills in the community and develop themselves according to their talents, interests, abilities and environment description above is one form of learning that has long characterized announced by the government which sharusnya as reference for practitioners of education to create a nation of character education.